Impact of climate risk on fiscal space: Do political stability and financial development matter? - John Beirne; Donghyun Park; Jamel Saadaoui; Mohammed Gazi Salah Uddin (Asian Development Bank (ADB), 2024)
We analyze the relationship between climate risk and fiscal space in a systematic and rigorous way. To do so, we use panel local projections to examine the role of political stability and financial development in the relationship. For a sample of 199 economies in 1990-2022, we first empirically confirm that climate risks adversely affect fiscal space. We find that such effects are most pronounced for the economies that are most vulnerable to climate change. However, our evidence indicates that political stability and financial development can mitigate such effects. We also identify nonlinearities in the climate risk- fiscal space nexus. More specifically, the impact of climate risk on fiscal space is greater when fiscal space is most constrained-i.e., in the upper quantile of the distribution. While fiscal consolidation is the key to mitigating the adverse effect of climate risks on fiscal space, our results suggest both political stability and financial development can contribute as well.
Keywords: F32; F41; F62; 330; climate risk; institutional quality; fiscal space; bond yields; sovereign ratings